A paternidade autoral em Memórias Póstumas de Brás Cubas no contexto do modelo realista-naturalista do século XIX - Moraes, Rosemary Aparecida de Almeida (2008)
The purpose of this study is to investigate how the authoral division is processed in the romance Memórias Póstumas de Brás Cubas and what it represents to the realistic-cienficist literary patterns of the XIX century. Having as a central focus the questioning about the authorial signature, the critical analysis concentrated itself in the strategies of this authorial dissemination through three basic principles: the duplicity of the opening prologues between Brás Cubas supposed author and Machado de Assis the authorial signature inscribed in the book; the fiction of the dead author and the conception of autobiography as a portrait of the real author, questioning the frontiers between the fictional and empirical author; the truncated citations and the continuous dislocations of the supposed author Brás Cubas to the function of reader of his own book, which turns the reader into an author, promoting a corrosion of the authorial unity. As a conclusion, the study demonstrated that the questioning of the authorial signature in Memórias Póstumas was an instabilizing element of the romance standard in the realism-naturalism of the XIX century, also affecting the criticism of the sources by means of the authorial reading fiction responsible for the gnawing citations of an author-reader that speaks to us from the other side of the mistery